T1 Mapping Quantifies Spinal Cord Compression in Patients With Various Degrees of Cervical Spinal Canal Stenosis - Maier, Ilko L.; Hofer, Sabine; Eggert, Eva; Schregel, Katharina; Psychogios, Marios-Nikos; Frahm, Jens; Bähr, Mathias; Liman, Jan (Frontiers in Neurology, 2020)
Age-related degeneration of the cervical spinal column is the most common cause of spinal cord lesions. T1 mapping has been shown to indicate the grade and site of spinal cord compression in low grade spinal canal stenosis (SCS). Aim of our study was to further investigate the diagnostic potential of a novel T1 mapping method at 0.75 mm resolution and 4 s acquisition time in 31 patients with various grades of degenerative cervical SCS. T1 mapping was performed in axial sections of the stenosis as well as above and below. Included subjects received standard T2-weighted MRI of the cervical spine (including SCS-grading 0-III), electrophysiological and clinical examination. We found that patients with cervical SCS showed a significant difference in T1 relaxation times within the stenosis (727 ± 66 ms, mean ± standard deviation) in comparison to non-stenotic segments above (854 ± 104 ms, p<0.001) and below (893 ± 137 ms, p<0.001). There was no difference in mean T1 in non-stenotic segments in patients (p=0.232) or between segments in controls (p=0.272). Mean difference of the T1 relaxation times was significantly higher in grade III stenosis (234 ± 45) vs in grade II stenosis (176 ± 45, p=0.037) vs in grade I stenosis (90 ± 87 ms, p=0.010). A higher difference in T1 relaxation time was associated with a central efferent conduction deficit. In conclusion, T1 mapping may be useful as a tool for SCS quantification in all grades of SCS, including high-grade stenosis with myelopathy signal in conventional T2-weighted imaging.